Spectrophotometric Determination of Tropicamide in Bulk and Pharmaceutical Formulations: Determination of tropicamide - Amanlou, Massoud; Souri, Effat; Izady, Shiva; Farsam, Hassan (Iranian Journal of Pharmaceutical Sciences, 2007)
Asimple and sensitive extractive spectrophotometric method is described fordetermination of tropicamide. The method is based on the reaction of tropicamideand bromocresol green. The ion-paired colored complex was extracted withchloroform at pH 3. The extracted complex showed maximum absorbance at 423nm. The complex was stable up to 2 days and obeyed Beer's law over theconcentration ranges of 1.32-100.81 μg/ml. No significant interference was observedfrom the excipients, coloring and flavoring agents commonly used in the tropicamidepharmaceutical preparations. The proposed method was applied successfully fordetermination of tropicamide in commercial eye drop dosage forms.